EXTH-44. PERSONALIZED IMMUNOTHERAPY VACCINES FOR GLIOBLASTOMA AND THEIR TREATMENT EFFICACY. (14th November 2022) - Trivedi, Vrunda; Yang, Changlin; Fenton, Graeme; Yegorov, Oleg; Von Roemeling, Christina; Klippel, Kelena; Ogando-Rivas, Elizabeth; Castillo, Paul; Hoang-Minh, Lan; Dyson, Kyle; Moore, Ginger; Mitchell, Duane
Abstract: BACKGROUND: Glioblastoma multiforme (GBM) remains a disease with debilitating survival outcomes. Cancer immunogenomics represents a complementary approach to the application of genomics in developing novel immunotherapies for brain malignancies. Using a cancer immunogenomics approach that we developed, called the O pen R eading Frame A ntigen N etwork (O.R.A.N.), we identified the immunogenic neoantigens and tumor-associated antigens (TAAs) including cancer-testis and developmental antigens, that are aberrantly overexpressed in murine models of GBM. The aim of this study is to evaluate the immunologic effects and safety of immunotherapy vaccines targeting neoantigens and TAAs in preclinical models of GBM. METHODS: RNAseq and WES were performed for murine glioblastoma tumors- KR158-Luc and GL261, and the results were fed to the O.R.A.N pipeline for antigen prediction. A tumor antigen-specific RNA library was created for each tumor using a gene enrichment strategy and validated by RNAseq. Tumor-bearing animals were treated with adoptively transferred ex vivo expanded lymphocytes and dendritic cell vaccines loaded with the tumor antigen-specific RNA. Tumor volume, and thus progress, was determined using in vivo luciferase imaging technique and the survival outcomes were noted. We also evaluated the efficacy of the tumor vaccines in combination with checkpoint blockade therapy by treating tumor-bearing animals with dendritic cell vaccines loaded with the tumor antigen-specific RNA combined with an anti-PD-1 antibody. RESULTS: The dendritic cell vaccines loaded with tumor antigen-specific RNA were significantly effective in slowing the progression of murine GBM tumors in combination with both the adoptive cellular therapy as well as checkpoint blockade therapy. Additionally, we identified antigen-specific T cells targeting several of our predicted antigens and an increase in tumor-infiltrating lymphocytes and memory T cells in the treated animals. CONCLUSION: We developed a dendritic cell-based vaccination approach targeting neoantigens and TAAs identified as being tumor-specific and evaluated the efficacy of immunotherapy vaccines in preclinical models of GBM.